Isolation and Screening of Diesel Degrading Bacteria from Ship Dismantling Facility at Tanjungjati, Madura, Indonesia - Harmin Sulistiyaning Titah; Herman Pratikno; Atiek Moesriati; Muhammad Fauzul Imron; Rizky Islami Putera (Journal of Engineering and Technological Sciences, 2018)
The ship dismantling industry is a cause of contamination of the environment by diesel. The objectives of this study were to isolate and screen diesel degrading bacteria from diesel contaminated areas. Diesel contaminated seawater and soil samples were collected from a ship dismantling facility at Tanjungjati, Madura, Indonesia. Isolation was conducted with an aseptic technique and growing the mixture culture was carried out based on the pour plate method. After 24 h of incubation, thirteen bacteria strains were isolated from diesel contaminated seawater and soil samples from the area of study. The isolated bacteria were identified based on morphological characterization. Mostly gram positive bacteria were found. The isolated bacteria were screened by using nutrient agar medium containing various diesel concentrations (0%, 5%, 10%, and 15% (v/v)). The result of the screening test showed that the bacteria coded EL and CT displayed the best resistance and highest growth in diesel polluted medium. It was shown that both of them potentially have a higher capability of utilizing diesel as carbon and energy source than the others.